Translation of a minigene in the 5′ leader sequence of the enterohaemorrhagic Escherichia coli LEE1 transcription unit affects expression of the neighbouring downstream gene - Islam, Md. Shahidul (Portland Press Ltd., 2011)
The 5′ end of the major RNA transcript of the LEE1 operon of enterohaemorrhagic Escherichia coli contains ~170 bases before the AUG translation start codon of the first recognized gene, ler. This unusually long leader sequence carries three potential alternative AUG start codons. Using a lac fusion expression vector, we confirmed that the ler gene AUG is functional for translation initiation, and we checked for translation initiation at the three alternative AUG codons. Whereas two of the alternative AUG codons appear incompetent for translation initiation, we detected strong initiation at the third AUG, which is followed by one AAA codon and a UAG stop codon. The location of this very short two-codon open reading frame with respect to the ler translation start appears to be critical. Hence mutations that destroy the UAG stop codon, or short deletions between the UAG stop codon and the ler translation initiation region, result in big effects on ler expression. In the context of the full-length LEE1 operon leader sequence, translation of this very short two-codon open reading frame is necessary for optimal expression of the ler gene and for the subsequent interactions of enterohaemorrhagic Escherichia coli with host target cells.